Understanding the business of library acquisitions - Schmidt, Karen A. (American Library Association, 1999)
The process of obtaining materials for libraries is more complex than ever. The 1990s have witnessed dramatically reduced library budgets while the materials that libraries need have broadened immensely. Library staff must address issues of electronic publishing and licensing, automated communications with vendors, new producers of library materials, and increased possibilities for outsourcing. Stretching limited acquisitions dollars to maintain an appropriate library collection is without doubt a creative and difficult task. This book thoroughly documents the basic principles and practices of acquisitions, including such timeless topics as vendor selection and evaluation, approval plans, acquiring serials, gifts and exchanges, and out-of-print and antiquarian markets.
Keywords: Acquisitions (Libraries) -- United States.; Acquisitions (Bibliothèques) -- États-Unis.; LANGUAGE ARTS & DISCIPLINES -- Library & Information Science -- General.; Acquisitions (Libraries); United States; Aanschaf.; Bibliotheken.; Library & Information Science.; Social Sciences.; Selecao e aquisicao material (biblioteca)